Insights into the Halochromism of a Bithiophene π* Probe - Caroli-Rezende, M; Mera-Adasme, R; Dominguez-Caru, M (Elsevier B.V., 2019)
The positive halochromism of the solvatochromic 4-nitro-4′-(N,N-dimethylamino)-2,2′-bithiophene in acetone and 1-butanol was investigated by molecular dynamics simulations and quantum mechanics calculations. Interactions of the dye with the solvated sodium cation were found to have only a minor effect on the observed halochromism, which was ultimately ascribed to a predominant interaction between iodide anions and the N,N-dimethylamino group of the dye. © 2019